Experience of adapting and implementing an evidence‐based nursing guideline for prevention of diaper dermatitis in a paediatric oncology setting. Issue 2 (10th June 2013) - Espirito Santo, Anelise; Choquette, Anne
Abstract Background Diaper dermatitis is one of the most common skin problems in children often caused by irritants that promote skin breakdown, such as moisture and faecal enzymes. It has been estimated that the incidence of diaper dermatitis is as high as 50% in children receiving chemotherapy. The scientific literature suggests a variety of preventative measures, but only a minority are systematically tested and supported by clinical evidence. Aim The purpose of this paper is to adapt and implement a skincare guideline to better prevent diaper dermatitis in the paediatric oncology population. Methods The Knowledge to Action process was used to guide the adaptation and implementation of the new guideline. As part of this process, different tools were used to identify and review selected knowledge (Appraisal of Guidelines Research Evaluation instrument), to tailor and adapt knowledge to the local context (ADAPTE process), to implement interventions (Registered Nurses' Association of Ontario toolkit) and to evaluate outcomes (qualitative analysis). The main outcomes measured included implementation of the guideline and nursing practice change. Results The guideline was successfully implemented as reported by nurses in focus group sessions and as measured by changes in nursing documentation. Conclusion The implementation of the guideline was successful on the account of the interplay of three core elements: The level and nature of the evidence; the context in which the research was placed; the method in which the process was facilitated.